Meningkatkan Kualitas Belajar Anak Menggunakan Metode Air (Auditory, Intellectually, Refetition) Pada Kelas IV SD - Rambe, Syarifah Ainy (Malewa: Journal of Multidisciplinary Educational Research, 2023)
Applying the AIR (Auditory, Intellectually, Reflection) method, teachers can make good use of media in classroom learning, getting responses from every teacher at SD Negeri 3 Kebayakan, such as when learning using media has a positive impact and makes the teaching and learning process easier. The type of research carried out is classroom action research (PTK). Classroom Action Research (PTK) is part of action research. The AIR (Auditory, Intellectually, Repetition) method can improve the quality of student learning in Class IV of SD Negeri 3. The prevalence of thematic sub-thematic learning, such as where I lived in my area, Learning 1 can be said to be good, there is evidence of the increase in student learning outcomes which was initially 45, 5 with a completion percentage of 10.4% until cycle I reached 68.2 with a completion percentage of 37.8% in social studies learning, while in cycle II it increased to 81.3, the completion percentage was 78.3%. In the Indonesian language subject, it was initially 70 with a percentage of 37.8%, then in cycle 1 it reached 71.43, with a completion percentage remaining at 41.1%, while in cycle II there was 82.8, with a completion percentage of 94.7%. Likewise, initially it was 84 with a completion percentage of 41.7% in science subjects, then in cycle I it was 69.0 with a completion percentage of 42.1% and increased to a completion percentage of 89.2% in cycle II.